Ekklesia in the Midst of Public Outrage Today - Bloomquist, Karen L. (Dialog, 2012)
How are recent widespread movements of public outrage a wake-up call to churches? Where are there similarities between these movements and what the church is called to be about? How can false gods, hopes, and desires be exposed pastorally? How can the “subversive remembering” of Word and sacrament bring depth to accompany these movements and meaning to the downturns or betrayal of the” American dream” that people are experiencing?